Α1 Antitrypsin deficiency and liver disease in childhood: genetic, immunochemical, histological, and ultrastructural diagnosis. Issue 6 (June 1974) - Milford, A.; Underwood, J. C. E.
Abstract : α1 Antitrypsin deficiency is a significant factor in the pathogenesis of neonatal cholestasis and progressive juvenile cirrhosis. The diagnosis may be suggested by the liver biopsy appearances and confirmed by immunochemical analysis of the serum. Genetic counselling of affected families is of importance, as medical treatment is ineffective at the present time.